Biochemical characterization of an acetylesterase from Bacillus subtilis and its application for 7-aminocephalosporanic acid deacetylation - Wang, Xiaoliang; Nong, Sujin; Li, Jiayi; Liu, Yan; Wu, Qian; Huang, Zunxi; Xu, Bo; Ding, Junmei (Frontiers in Microbiology, 2023)
Deacetyl-7-aminocephalosporanic acid (D-7-ACA), which could be converted from 7-aminocephalosporanic acid (7-ACA), is a crucial starting material for synthesizing industrial semisynthetic β-lactam antibiotics. Enzymes responsible for the conversion of 7-ACA to D-7-ACA present critical resources for medical industry. Here, a putative acetylesterase, EstSJ, identified from Bacillus subtilis KATMIRA1933 was firstly heterogeneously expressed and biochemically characterized. EstSJ belongs to carbohydrate esterase family 12 and is active on short-chain acyl esters from p-NPC2 to p-NPC6. Multiple sequence alignment showed that EstSJ was also an SGNH family esterase with a typical GDS(X) motif at its N-terminal and a catalytic triad composed of Ser186-Asp354-His357. The purified EstSJ displayed the highest activity of 1783.52 U mg-1, at 30℃, pH 8.0, and stabilized within pH 5.0–11.0. EstSJ can deacetylate the C3' acetyl group of 7-ACA to generate D-7-ACA, and the deacetylation activity was 4.50 U mg-1. Based on structural and molecular docking with 7-ACA, the catalytic triads together with four substrate-binding residues of EstSJ (Asn259, Arg295, Thr355, and Leu356) are revealed. This work provided a promising 7-ACA deacetylase candidate which could be applied for production of D-7-ACA from 7-ACA in pharmaceutical industry.